Silent Memories Traumatic Lives: Ukrainian migrant refugees in Western Australia - Melnyczuk, Lesa (Western Australian Museum, 2012)
Silent Memories, Traumatic Lives is a quest for understanding, an attempt to make sense of the very emotional history of the Ukrainian post-war migrants to Western Australia. Ukrainian migrants arrived in Australia by ship between 1947 and 1951, from the Displaced Persons camps of Europe, survivors of the worst of the Soviet regime's atrocities, including genocidal famine, and only recently released from forced unpaid labour under the German Nazi regime. The testimonies of Ukrainian famine survivors included in this book reflect the findings of similar studies carried out in Ukrainian communities throughout the world. This work adds to mounting evidence of the genocidal nature of the Ukrainian famine of 1932 - 1933 and the lasting effects it has had on survivors.